Design and analysis of plasmonic nanostub filter using metal-insulator- met-al (MIM) waveguide - Suraya Mubeen, Dr (International Journal of Engineering and Technology, 2018)
Metal-insulator-metal (MIM) silicon based nanostub structures have been designed and analyzed using the finite difference time-domain (FDTD) technique. An analytic model is discussed which is based on the resonance theory. Numerical results show double and single narrow band transmissions for small and long lengths of nanostub, respectively. The transmission band of the structure is controlled by varying the width and the length of the nanostub. These MIM nanostub structure can have potential applications in nanoscale high density photonic integrated circuits (PICs).Â Â